The European Nucleotide Archive in 2020. Issue Volume 49:Issue D1(2021) (11th November 2020) - Harrison, Peter W; Ahamed, Alisha; Aslam, Raheela; Alako, Blaise T F; Burgin, Josephine; Buso, Nicola; Courtot, Mélanie; Fan, Jun; Gupta, Dipayan; Haseeb, Muhammad; Holt, Sam; Ibrahim, Talal; et al.
Abstract: The European Nucleotide Archive (ENA; https://www.ebi.ac.uk/ena ), provided by the European Molecular Biology Laboratory's European Bioinformatics Institute (EMBL-EBI), has for almost forty years continued in its mission to freely archive and present the world's public sequencing data for the benefit of the entire scientific community and for the acceleration of the global research effort. Here we highlight the major developments to ENA services and content in 2020, focussing in particular on the recently released updated ENA browser, modernisation of our release process and our data coordination collaborations with specific research communities.